(untitled) (Journal of Hama University, 2022)
Hospital-acquired infections are the main cause of death and disability for patients, although they can be prevented. Healthcare -related infection causes many consequences for patients, causing more suffering, complications, and treatments, in addition to an increase in hospitalization periods .The study aimed to reveal the effect of applying chlorhexidine solution versus povidone in preventing infections associated with central venous.The research was conducted in intensive care units ( internal care , surgical care , cardiac surgery care ) at Tishreen University Hospital, city. Lattakia from 15/7/2020 to 29/6/2021Where the research was conducted on a sample of 40 patients in the intensive care units, the sample was taken using the available sample method . Two tools were used( Clinical Health Assessment Form ) and ( Central Venous Catheter-associated Sepsis Monitoring Form ).The results of the study showed : There is a slight superiority of chlorhexidine over povidone in preventing infection associated with central venous catheterization. The laboratory results of the study showed that there is a statistically significant superiority of chlorhexidine over povidone . There were no significant statistically significant differences regarding the effect of the two solutions in relation to the general scores .The results of the current study showed a decrease in the incidence of local infection signs ( oozing , pain , redness , ulceration ) in patients of two groups for the third day and the fifth day with almost the same level .Designing training programs for nursing staff on methods of managing and preventing central venous catheter insertion site infections and directing hospitals to activate protocols for using chlorhexidine solution in preparation for the central venous catheter insertion site and changing dressings